Seasonal Influence on Semen Production Performance of Crossbred Buck (Saanen  Beetal) in an Organized Farm - Narwade, Baban Madhavrao; Mohanty, Tushar Kumar; Bhakat, Mukesh; Rahim, Abdul; Sinha , Ranjana; Singh, Amit Kumar (International Journal of Livestock Research, 2018)
Season plays an important role in semen production performance of caprines due to change in temperature, humidity, hormone level, vegetation and nutritional availability. Therefore, the present study was planned on five crossbred bucks (Saanen ´ Beetal) maintained at Livestock Research Centre, ICAR-NDRI, Karnal to evaluate seasonal effect (cold-humid winter: November-March; hot-dry summer: April-June; hot-humid summer: July-October) on fresh semen quality. Data on 625 ejaculates from five adult bucks (125×5) were collected for semen quality analysis and data was analyzed by using least square analysis. The mean ejaculate volume, mass activity (MA), progressive motility, live sperm percent, sperm concentration, hypo-osmotic swelling test (HOST) and intact acrosome percent were 1.05 ml, 3.28, 76.69%, 77.72%, 3.06´109/ml, 69.4% and 94.71%, respectively. There was significant individual variation of all fresh semen quality parameters among the bucks (p<0.05). It was observed that colour of semen was creamy with thick consistency during winter season, while slightly thin creamy during both hot-dry and hot- humid summer seasons. The semen volume in winter season was significantly (p<0.05) lower and higher in hot-dry summer. However, other parameters like MA, progressive motility, live sperm percent, sperm concentration and HOST positive sperm percent were significantly (p<0.05) higher in winter season but the values remained on lower side during hot-dry summer seasons but intact acrosome percent remained lower in hot-humid season. It can be concluded that there is individual variation in semen quality and winter season produces better quality semen fallowed by hot humid and hot dry season.